Penerapan Seci Model pada Analisa Pembangunan Kontrusi Bangunan - Sofaliana, Fresa Dwi Juniar (STIKOM Tunas Bangsa Pematangsiantar, 2022)
This study aims to find out how a construction worker can expertly build a strong home foundation as a building foundation with land. Keah This study aims to find out how a construction worker can expertly build a strong home foundation as a building foundation with soil. That expertise is very difficult to come by every person who needs it, because the experience of experience in someone is very different from the theory he learned. For that reason, the delivery of knowledge from someone who has experience in the construction of foundations and can be obtained easily by those who need it, Knowledge Sharing from informants. This study aims to find out how a construction worker can expertly build a strong home foundation as a building foundation with land. That expertise is very difficult to come by every person who needs it, because the experience of experience in someone is very different from the theory he learned. For that reason, the delivery of knowledge from someone who has experience in the construction of foundations and can be obtained easily by those who need it, Knowledge Sharing from determined informants who will be poured into the program, knowledge of their experiences during their career in building construction. To get descriptive data from informants who will be transferred knowledge, this study uses qualitative research methods because it based on the results of knowledge of interviews while the knowledge management method uses the method of Socialization, Externalization, Combination and Internalization (SECI), in the process of analysis and application design using Unifield Modeling Language (UML) modeling tools. The results achieved in the form of an analysis application of the costs and materials needed for the construction of a house foundation, so that there is not much raw material that is not used and is also time consuming when lacking in materials because it has been analyzed by the application of R.A.B Foundation. Through this application, documentation of one's experience will be displayed so that it is easier for people who are not proficient and understand this problem so that it will become a knowledge repository